Innovation of Mix Mango-Spirulina Smoothies as a Modern Functional Beverage Towards Creative Economy - Jumrodah Jumrodah; Akhmad Mujahid; Nadia Uswatun Jayanti; Nor Rezqiyatun Najhah; Nuridah Nuridah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The global shift toward healthy lifestyles has accelerated the development of functional beverages that not only provide basic nutrition but also deliver additional physiological benefits. Fruit-based beverages are widely consumed due to their sensory appeal; however, many commercial products remain high in sugar while lacking sufficient protein and essential micronutrients. Therefore, integrating nutrient-dense natural ingredients such as Spirulina into fruit-based smoothies represents a promising scientific approach to enhance nutritional quality and functional value.This study aimed to develop a mango–Spirulina smoothie as a modern functional beverage and to evaluate consumer acceptance of its sensory attributes. A descriptive qualitative approach was applied. Spirulina sp. was cultivated in the Aquatic Biota Cultivation Laboratory, while smoothie formulation was conducted in the Entrepreneurship Laboratory of Universitas Islam Negeri Palangka Raya. Organoleptic and consumer acceptance tests were carried out with 30 respondents, assessing color, taste, texture, aroma, and overall preference. The results showed that the smoothie exhibited a slightly green color (90%), sweet taste (100%), and smooth texture (90%). Although aroma acceptance was relatively low, with 47% of respondents rating it as not fragrant, overall consumer acceptance was high, with 73% indicating “like” and 27% “very like.” In conclusion, the mango–Spirulina smoothie demonstrates strong potential as a modern functional beverage with good sensory acceptance and prospects for development within the creative economy. Further studies are recommended to improve aroma quality and to conduct quantitative nutritional analysis to support product commercialization.